Future Directions in Semiconductor Processing: Scaling, Integration, and the Sustainability Imperative - Ramatu Al-hassan; Edmun Dasori Azundow; Yaw Amankrah Sam-Okyere; Emmanuel Osei-Kwame; Nii Ayitey Freddie Aryee (Applied Engineering, Innovation, and Technology, 2026)
The global semiconductor industry has navigated a period of intense innovation and systemic challenges between 2020 and 2025. Driven by the exponential demands of Artificial Intelligence (AI), 5G/6G communication, and high-performance computing (HPC), the sector has pursued a dual strategy of continued transistor scaling and sophisticated heterogeneous integration. This review systematically analyzes the critical advancements and challenges within this period. We detail the fundamental architectural shift from FinFET to Gate-All-Around (GAA) transistors, enabling the 3-nanometer (nm) and 2-nm nodes, and the adoption of Extreme Ultraviolet (EUV) lithography for High-Volume Manufacturing (HVM). Concurrently, advanced packaging techniques, such as hybrid bonding and the standardization of chiplet architectures via the Universal Chiplet Interconnect Express (UCIe), have emerged as indispensable means to circumvent planar scaling limits. Economically, the industry has contended with escalating capital expenditure (CapEx) and the severe global chip shortage (2020–2023), prompting widespread government intervention, notably through the U.S. CHIPS Act and the EU Chips Act. Crucially, the review addresses the intensifying sustainability mandate, examining the challenges posed by high-Global Warming Potential (GWP) gas emissions, soaring water consumption, and the necessary transition toward circular economy principles within the fabrication environment. The findings underscore that future progress is contingent upon balancing relentless performance demands with resilient supply chains and comprehensive environmental stewardship.